VACCINE PROPHYLAXIS OF PNEUMOCOCCAL INFECTION AS ONE OF THE REASONS OF COMPLICATIONS AND MORTALITY IN PATIENTS WITH INFLUENZA - M.P. Kostinov; D.V. Pakhomov; O.O. Magarshak; M.V. Sukhinin (Вопросы современной педиатрии, 2009)
Authors give characteristics of pathogenetic and clinical correlations between influenza and pneumococcal infection. The results of analysis of data from international studies, confirming the role of pneumococcal infection as main reason of mortality during the influenza pandemiс of 1918 year are presented. The role of vaccination against pneumococcal infection with the use of pneumococcal conjugated 7-valent vaccine in children under 5 years old and polysaccharide 23-valent vaccine in adults undergoing high risk factors, for the purpose of influenza complications including new high-pathogenic influenza A/H1N1 California, is shown.Key words: children, influenza, pneumococcal infection, vaccination.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(6):131-134)